THE ROLE OF SPORT PARTICIPATION AND BODY MASS INDEX IN PREDICTING MOTOR COMPETENCE OF SCHOOL-AGE CHILDREN - Ferreira, Luciana; Vieira, José Luiz Lopes; Silva, Pâmela Norraila Da; Chaves, Raquel Nichele De; Fernandes, Romulo Araújo; Cheuczuk, Francielle; Rocha, Francielli Ferreira Da; Caçola, Priscila (Universidade Estadual de Maringá, 2019)
The purpose of this study was to investigate the association between Sport Participation (SP) and Motor Competence (MC) in school-age children, and to assess the mediation role of Body Mass Index (BMI) on this association. 707 children (332 boys, 375 girls) aged between 6- to 10 years participated in the study. Motor competence was determined using the Bruininks-Oseretsky Test of Motor Proficiency (BOT-2). Parents were asked about organized SP, categorized as 1) no participation, 2) partial participation and 3) consistent participation, and BMI was calculated based on the child’s height and weight. The results indicated significant differences for all MC components and total score for SP categories, all p < .05, with higher results for consistent participation in sports. For BMI, significant differences occurred in all components, with the exception of fine manual control and manual coordination. Our findings showed that SP was associated with MC, and BMI was not an important factor in these relationships. However, a small mediation of BMI was found, but only for obese children. In summary, we conclude that sport participation plays a relevant role in the development of motor competence in school-age children, and that association is, in general, not mediated by weight status.

O objetivo deste estudo foi investigar a associação entre Participação Esportiva (PE) e Competência Motora (CM) em crianças em idade escolar e avaliar o papel da mediação do Índice de Massa Corporal (IMC) nesta associação. Foram avaliadas 707 crianças (332 meninos, 375 meninas) com idades entre 6 e 10 anos participaram do estudo. A competência motora foi determinada usando o Teste Bruininks-Oseretsky de Proficiência Motora (BOT-2). Os pais foram questionados sobre a SP organizada, categorizada como 1) sem participação, 2) participação parcial e 3) participação consistente, e o IMC foi calculado com base na altura e no peso da criança. Os resultados indicaram diferenças significativas para todos os componentes do CM e escore total para as categorias de PS, todos p <0,05, com resultados mais altos para a participação consistente nos esportes. Para o IMC, ocorreram diferenças significativas em todos os componentes, com exceção do controle manual e da coordenação manual. Nossos achados mostraram que a SP estava associada à CM, e o IMC não foi um fator importante nessas relações. No entanto, uma pequena mediação do IMC foi encontrada, mas apenas para crianças obesas. Concluímos que a participação esportiva desempenha um papel relevante no desenvolvimento da competência motora em crianças em idade escolar, e essa associação, em geral, não é mediada pelo status de peso.
O PAPEL DA PARTICIPAÇÃO ESPORTIVA E DO ÍNDICE DE MASSA CORPORAL NA PREDIÇÃO DA COMPETÊNCIA MOTORA DE CRIANÇAS EM IDADE ESCOLAR
Keywords: Motor competence; Body mass index; Sport participation; School-age children; Competência motora; Índice de massa corporal; Participação esportiva; Crianças em idade escolar